Peranan (Bp4) dalam Membina Keluarga Sakinah dan Penyelesaian Penyelisihan Perkawinan Islam - Jamilah, Fitrotin (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2019)
The marriage advisory and preservation advisory body is a semi-official organization that supports the duties of the ministry of religion in the field of marriage and aims to enhance the quality of marriage and create a happy, prosperous and eternal family or household according to Islamic teachings while marriage disputes are a household relationship between husband and disputed wives in marriages and the purpose of this case study is to discuss 1) the marriage counseling and preservation advisory body 2) the role of marital advisory and preservation advisory bodies 3) marital disputes and the role of BP4 in marital dispute resolution. The role of BP4 in resolving marital disputes over marital disputes is: BP4 acts as a marriage consultant, by providing explanations, guidance to the disputing parties, namely guardians, with the bride and groom through the Marriage Advisory Board, Marriage Counseling and Preservation Agency (BP4). Of the five cases handled by BP4 that could be reconciled and all parties received reunification of the family that was fostered (no divorce occurred, there were 4 cases (80%) and for which the divorce process continued there was 1 case (20%). BP4 in carrying out its duties certainly experienced obstacles. These obstacles are internal to BP4 itself, which tends not to be pro-active in finding families whose marriages are experiencing problems.